8D.01: EFFECTS OF ANGIOTENSIN-CONVERTING ENZYME 2 ON RENAL OXIDATIVE STRESS LEVELS IN APOLIPOPROTEIN E-DEFICIENT MICE. (June 2015) - Zhong, J.; Chen, L.J.; Zhang, Z.Z.; Xu, Y.L.; Xu, R.; Song, B.; Gao, P.J.; Zhu, D.L.; Oudit, G.Y.
Abstract : Objective: The renin-angiotensin system (RAS) has been known for more than a century as a cascade that regulates body fluid balance, renal functions and blood pressure. Angiotensin-converting enzyme 2 (ACE2) is now known as a negative regulator of RAS, and activation of the ACE2 is a possible alternative target for new drugs, since some protective influences on renal and cardiovascular function have been revealed. We hypothesized that ACE2 would exert beneficial effects on oxidative stress levels and renal injury in apolipoprotein E (ApoE) -knockout (KO) mice. Design and method: In this study, we used 12-week-old wild-type, ApoEKO, and ACE2/ApoE double KO mice. The ApoEKO mice were treated with recombinant human ACE2 (hrACE2) with the daily dose of 2 mg/kg. We characterized the functional, structural and molecular signaling changes in mice kidneys. Results: Compared with the ApoEKO mice, ACE2 deficiency led to greater increases in renal oxidative stress levels and expression of oxidative stress-inducible proteins NADPH oxidase 4 (NOX4) in the ACE2/ApoE double KO mice. These changes were associated with exacerbation of renal tubule ultrastructure injury and greater activation of Akt and ERK1/2 phosphorylated signaling. Conversely, treatment with hrACE2 significantly attenuated renal oxidative stress levels and ultrastructure injury, and prevented the expression of NOX4 and phosphorylated level of Akt and ERK1/2 in ApoEKO mouse kidneys. However, there were no changes in renal expression of NOX2 and Mas receptor among groups. Conclusions: Deletion of ACE2 triggers greater increases in renal oxidative stress and tubular ultrastructure injury in the ACE2/ApoE double mutant mice with greater activation of Akt-ERK1/2 phosphorylated signaling. While ACE2 overexpression alleviates renal tubular injury in ApoE-mutant mice with suppression of superoxide generation and downregulation of the Akt-ERK phosphorylated signaling. Strategies aimed at enhancing ACE2 action may have important therapeutic potential for atherosclerosis and renal diseases.